A historical survey of the fundamental theorem of arithmetic - Agargün, AG; Özkan, EM (ACADEMIC PRESS INC, 2001)
The purpose of this article is a comprehensive survey of the history of the Fundamental Theorem of Arithmetic. To this aim we investigate the main steps during the period from Euclid to Gauss. (C) 2001 Acidemic Press.
Keywords: al-Farisi; Euclid; Fundamental Theorem of Arithmetic; History & Philosophy of Science; Mathematics